2022
DOI: 10.1186/s12864-021-08243-4
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the long noncoding RNA-associated competitive endogenous RNA network in the osteogenic differentiation of periodontal ligament stem cells

Abstract: Backgroud The mechanism implicated in the osteogenesis of human periodontal ligament stem cells (PDLSCs) has been investigated for years. Previous genomics data analyses showed that long noncoding RNA (lncRNA), microRNA (miRNA) and messenger RNA (mRNA) have significant expression differences between induced and control human PDLSCs. Competing for endogenous RNAs (ceRNA), as a widely studied mechanism in regenerative medicine, while rarely reported in periodontal regeneration. The key lncRNAs an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 66 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…Zheng et al 14 identified over 200 differentially expressed ln-cRNAs in PDLSCs during osteogenic differentiation at 3, 7, and 14 days, and another 14 mRNA and 8 lncRNA expression profiles were time-dependent. In a similar study, Lai et al 16 discovered 994 upregulated lncRNAs, 1578 upregulated mRNAs, and 30 upregulated miRNAs, as well as 1177 downregulated lncRNAs, 1979 downregulated mRNAs, and 86 downregulated miRNAs in PDLSCs following osteogenic induction. Further analysis revealed the involvement of MAPK and TGF-β signaling pathways in the osteogenic differentiation of PDLSCs.…”
Section: S Ig Naling Pathways Involving In N Crna S Reg Ul Ati On In ...mentioning
confidence: 85%
See 2 more Smart Citations
“…Zheng et al 14 identified over 200 differentially expressed ln-cRNAs in PDLSCs during osteogenic differentiation at 3, 7, and 14 days, and another 14 mRNA and 8 lncRNA expression profiles were time-dependent. In a similar study, Lai et al 16 discovered 994 upregulated lncRNAs, 1578 upregulated mRNAs, and 30 upregulated miRNAs, as well as 1177 downregulated lncRNAs, 1979 downregulated mRNAs, and 86 downregulated miRNAs in PDLSCs following osteogenic induction. Further analysis revealed the involvement of MAPK and TGF-β signaling pathways in the osteogenic differentiation of PDLSCs.…”
Section: S Ig Naling Pathways Involving In N Crna S Reg Ul Ati On In ...mentioning
confidence: 85%
“…A growing body of evidence has shown that numerous ncRNAs were closely associated with the osteogenic differentiation of periodontal tissue-derived cells and were involved in multiple signaling pathways, including the Wnt, BMP/Smad, NF-κB, and PI3-K/Akt/mTOR pathways. [11][12][13][14][15][16][17][18] In this review, we summarized these signaling pathways that ncRNAs regulate in osteogenic differentiation of periodontal tissue-derived cells, providing new ideas for the future treatment of periodontitis and periodontal regeneration (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By inhibiting the expression of miRNAs, lncRNAs can also play a regulatory role. During the osteogenic differentiation of PDLSCs, lncRNAs can act as ceRNAs and form networks to regulate the Wnt/β-catenin signaling pathway 97 . lncRNA-ANCR competitively binds miR-758 and inhibits the expression of Notch2, which further affects the Wnt/β-catenin signaling pathway and inhibits the osteogenic differentiation of PDLSCs 98 .…”
Section: 321lncrnamentioning
confidence: 99%
“…As the complex regulatory mechanisms of lncRNAs and their biological functions are not fully understood, more studies have concentrated on using vectors to deliver small ncRNAs for bone defect repair. However, several recent studies have shown that lncRNAs can affect the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) through a mechanism known as competing endogenous RNAs (ceRNAs), which has received increasing attention (Hong et al, 2020;Lai et al, 2022;Wang et al, 2020b. The experimental results of Ouyang et al (2020) showed that lncRNA ENST00000563492 can act as a ceRNA for miR-205-5p to upregulate the expression of CDH11 and VEGF, thereby promoting the osteogenic differentiation of BMSCs.…”
Section: Introductionmentioning
confidence: 99%